Voice Recognition Powered Women’s Safety App - Dhivya, S; Ramnath, R; Redhanya, C; Sasi, S.; Priya, SL Sathiya (International Journal of Computer Sciences and Engineering, 2022)
Our idea is to design an application that will make each and every place, hour safer for women and children again. For their security and safety purpose, our government has provided security through rules and regulations in the society and there are many smart security systems existed. In this project we are designing a mobile application that can be used by women for help in emergencies as it contains an emergency alert button when it is pressed then it will automatically connect a call to the emergency contacts it also sends the live location of the user through normal message. This application also contains a voice alert through which the user can raise a voice and spell “help” 1 time so that automatically the message and the location will be shared to the emergency contacts which was registered.